Fenomena “Virtual Youtuber” Kizuna Ai di Kalangan Penggemar Budaya Populer Jepang di Indonesia - Dwiana Rachmadewi Puspitaningrum; Arie Prasetio (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2019)
Defy Media’s survey shows that 85% of 13-24 years old teenagers use YouTube as the main platform to watch videos. Hence, YouTuber became a favored profession. Within YouTuber profession trend, Virtual YouTuber phenomenon emerges. Virtual YouTubers are YouTubers who appear as 3D animation avatars. The term was first used by Virtual YouTuber Kizuna Ai whose popularity reaches Indonesia. Based on pre-research, 96 of 100 Indonesian Japanese pop-culture fans know Kizuna Ai, 86 has watched her vlogs, and 53 subscribe her YouTube channel. This research’s goal is to understand motives and meanings in watching Kizuna Ai’s vlogs. this study used Phenomenology method. Even though they are virtual, their presences can be captured by senses. Based on the research’s results, there are two kinds of motive in watching Kizuna Ai’s vlogs: because motives consisting interest motive and curiosity motive, and in-order-to motives consisting desire for information motive, self-actualization needs motive, competency motive, desire for entertainment motive, and self-existence needs motive. Meanwhile, the meanings in watching Kizuna Ai’s vlogs are ideal partner figure representation, escape from problems, interest in Japanese pop-culture representation, role-model for interacting with others, and the importance of being expressive and expressing opinions.